Gender Stereotype and Workplace Bias: A Case of Nepalese Commercial Bank - Yadav, Anuradha (Nepalese Journal of Business, 2025)
This study examines the gender stereotype and workplace bias: A case of Nepalese commercial bank. Workplace environment is selected as the dependent variable. Similarly, education, self-interest, influence of reference group, cultural factor and glass ceiling are selected as the independent variables. This study is based on primary data with 122 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing gender stereotype at workplace in Nepalese commercial bank. The study showed that education has a positive impact on workplace environment. It means that higher the education, better will be the workplace environment. Similarly, self-interest has a positive impact on workplace environment. It indicates that rise in self interest correlates with an improvement in the workplace environment. Moreover, influence of reference group has a positive impact on workplace environment. It means that increase in influence of reference group leads to increase in workplace environment. Likewise, cultural factor has a positive impact on workplace environment. It shows that increase in cultural factor leads to increase in workplace environment. Similarly, glass ceiling has negative impact on workplace environment. It shows that higher the glass ceiling, lower would be the workplace environment.